2014
DOI: 10.1098/rsob.130229
|View full text |Cite
|
Sign up to set email alerts
|

A CENP-S/X complex assembles at the centromere in S and G2 phases of the human cell cycle

Abstract: The functional identity of centromeres arises from a set of specific nucleoprotein particle subunits of the centromeric chromatin fibre. These include CENP-A and histone H3 nucleosomes and a novel nucleosome-like complex of CENPs -T, -W, -S and -X. Fluorescence cross-correlation spectroscopy and Förster resonance energy transfer (FRET) revealed that human CENP-S and -X exist principally in complex in soluble form and retain proximity when assembled at centromeres. Conditional labelling experiments show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 65 publications
1
25
0
3
Order By: Relevance
“…Thus, CENP-T could be assembled first onto replicated chromatin and later on recruit CENP-W/S/X. In vitro assays suggest the existence of multiple DNA binding sites in CENP-T and CENP-W. 28,38 While in human cells the assembly of the CENP-T/W/S/X complex on chromatin occurs in late S/G2 phase cells, 18,36 it may take place in mitosis in the egg extracts. Xenopus homologues of CENP-S and CENP-X are present in the database but no antibodies against them are available yet to test when they are recruited to centromeres.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, CENP-T could be assembled first onto replicated chromatin and later on recruit CENP-W/S/X. In vitro assays suggest the existence of multiple DNA binding sites in CENP-T and CENP-W. 28,38 While in human cells the assembly of the CENP-T/W/S/X complex on chromatin occurs in late S/G2 phase cells, 18,36 it may take place in mitosis in the egg extracts. Xenopus homologues of CENP-S and CENP-X are present in the database but no antibodies against them are available yet to test when they are recruited to centromeres.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 How CENP-T/W/S/X are targeted to the centromere is currently unclear although it has been reported that their incorporation occurs in late S phase/G2 and requires CENP-A. 18,35,36,39 It is also unclear whether they contribute to CENP-A deposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCAN remains associated with centromeric chromatin across the entire cell cycle (6)(7)(8). The CCAN includes CENP-A, CENP-C, and four multisubunit complexes: CENP-L/-N (9), CENP-H/-I/-K/-M (10), CENP-O/-P/Q-/R/-U (11), and CENP-T/-W/-S/-X (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…CENP-T and CENP-W completely turn over during S phase, but increase in abundance in S/G 2 relative to G 1 (Prendergast et al 2011). CENP-S and CENP-X also assemble at centromeres during S/G 2 (Dornblut et al 2014). CENP-N is stabilized specifically at the end of S phase through an unknown mechanism (McClelland et al 2007;Hellwig et al 2011).…”
Section: Centromere Longevity and Cenp-a Maintenance During Dna Replimentioning
confidence: 99%